Exploring the Spatial Agglomeration Characteristics and Determinants of Strategic Emerging Industries: Evidence from 12,979 Industrial Enterprises in China - Xiaofeng Zhao; Yanyan Wang; Ying Li; Sheng-Hau Lin; Haixia Shi (Systems)
Strategic emerging industries (SEIs) have the potential to be a nation’s leading industries in the post-industrialization era. Exploring the spatial distribution of SEIs and the impetuses of their location choice plays a key role in formulating policies conducive to regional industrial and economic development. However, most studies on relevant topics neglected the impact of institutional environment and local innovation on the formation of spatial patterns of SEIs. By investigating 12,979 industrial enterprises in China, this research applied spatial autocorrelation and spatial regression analysis to explore the spatial characteristics of SEIs and identify the variables affecting the location selection of SEIs that result in these spatial patterns. The findings indicated significant spatial differences in the spatial distributions and agglomeration patterns of SEIs. Institutional environment, local innovation, and regional economy have significant impacts on the location choice of SEIs. The interactive effects of local innovation and institutional environment on the spatial agglomeration of SEIs revealed that a higher degree of decentralization and stronger local innovation capability would promote a stronger agglomeration of SEIs. Regions with strong (weak) marketization and weak (strong) institutions of higher education would promote SEIs agglomeration. Based on the findings, policy options were suggested to facilitate SEIs planning and differentiated pathways of industrial transformation.